Conversation 2.0. and democracy. An analysis of reader’s comments in Catalan online newspapers (Communication & Society, 2010)
Audience participation in online newspapers can potentially revitalize democratic debates. However, a thorough analysis of the nature of this participation is still much needed. This article explores Conversation 2.0 through its most popular feature: reader comments in news. It analyzes the ethical and legal framework, and evaluates whether there is a pluralistic and respectful debate that fosters a democratic society. The content of a sample of stories from seven Catalan online newspapers suggests that this is not actually the case. The research project was commisioned by the Catalan Information Council, the institution protecting ethics in journalism in Catalonia.